Dreaming of Michelangelo : Jewish variations on a modern theme - Biemann, Asher D. (Stanford University Press, 2012)
Dreaming of Michelangelo is the first book-length study to explore the intellectual and cultural affinities between modern Judaism and the life and work of Michelangelo Buonarroti. It argues that Jewish intellectuals found themselves in the image of Michelangelo as an ""unrequited lover"" whose work expressed loneliness and a longing for humanity's response. The modern Jewish imagination thus became consciously idolatrous. Writers brought to life-literally-Michelangelo's sculptures, seeing in them their own worldly and emotional struggles. The Moses statue in particular became an a.